2014
DOI: 10.3390/polym6010243
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Poly(ester amide) (PEA) Microfibrils in Ocular Tissues

Abstract: Drug delivery systems (DDS) are able to deliver, over long periods of time, therapeutic concentrations of drugs requiring frequent administration. Two classes of DDS are available, biodegradable and non-biodegradable. The larger non-biodegradable implants ensure long-term delivery, but require surgical interventions. Biodegradable biomaterials are smaller, injectable implants, but degrade hydrolytically and release drugs in non-zero order kinetics, which is inefficient for long-term sustained drug release. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…We hypothesized that intradiscal application of PEAs in the avascular IVD would be well accepted, in line with previous studies showing a moderate subcutaneous tissue response to a hydrogel that showed no response at all upon intradiscal injection. 32 Furthermore, safe intravitreal application of PEA fibrils through a 26G needle was already shown by Kropp et al 13 Indeed, PEAMs were considered safe within a 6 months follow-up period, based on clinical signs, disc height index, T2 values, biomolecular and biochemical analyses, and IVD histopathology. The focal, mild granulomatous reaction described in one of the PEAM injected IVDs could have been a consequence of leakage of the PEAMs, the injection procedure itself, or it could have been a reaction consistent with the ongoing process of IVD degeneration.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We hypothesized that intradiscal application of PEAs in the avascular IVD would be well accepted, in line with previous studies showing a moderate subcutaneous tissue response to a hydrogel that showed no response at all upon intradiscal injection. 32 Furthermore, safe intravitreal application of PEA fibrils through a 26G needle was already shown by Kropp et al 13 Indeed, PEAMs were considered safe within a 6 months follow-up period, based on clinical signs, disc height index, T2 values, biomolecular and biochemical analyses, and IVD histopathology. The focal, mild granulomatous reaction described in one of the PEAM injected IVDs could have been a consequence of leakage of the PEAMs, the injection procedure itself, or it could have been a reaction consistent with the ongoing process of IVD degeneration.…”
Section: Discussionmentioning
confidence: 94%
“…The median histopathological grade of noninjected (12; range: 10-15), sham-injected (14; range: 11-17), and PEAMs-injected IVDs 13 (11)(12)(13)(14)(15) was not significantly different. Representative histopathological images (picrosirius red/alcian blue stain) of all conditions are shown in Figure 1(B', B'', C', C'', and D', D'').…”
Section: Histopathology and Biochemistrymentioning
confidence: 93%
See 2 more Smart Citations
“…Transparency is an inherent property of material, Ozcelik et al demonstrated that chitosan–PEG hydrogel films that can achieve more than 95% of optical transparency . Although nowadays there is some biodegradable ocular product for drug delivery and treatment, such as OZURDEX (Allergan, USA) which is made from PLGA and has been used clinically, no commercial biodegradable polymer film/membrane is available in the market for ocular regeneration or reconstruction.…”
Section: Requirements For Biodegradable Film and Membrane In Te Applimentioning
confidence: 99%